S65 The calcium-activated K+ channel KCa3.1 is expressed by component cells of lymphangioleiomyomatosis (LAM) nodules. (December 2018) - Naveed, S; Clements, D; Johnson, SR; Bradding, P
Abstract : Introduction and objectives: LAM is a rare, progressive interstitial lung disease characterised by progressive cystic destruction of the lung. There is currently no effective treatment for LAM. The hallmark lesion of LAM lung disease is the LAM nodule, a complex structure consisting of proliferating smooth muscle-like 'LAM cells', fibroblasts, lymphatic endothelial cells and inflammatory cells. KCa 3.1 ion channels are expressed by a number of structural airway and lung parenchymal cells including airway smooth muscle cells (ASM) and parenchymal fibroblasts, and are implicated in several cell processes including proliferation, migration, differentiation and collagen secretion. We hypothesise that KCa 3.1-dependent cell processes in LAM cells and LAM associated fibroblasts (LAFs) are a common denominator in the development of LAM nodules and the accompanying lung destruction. Methods: TSC null 621–101 LAM cells (human angiomyolipoma cell line) and primary LAFs were obtained from National Centre for LAM, Nottingham. We examined both cell types for the presence and activity of KCa 3.1 channels using q-PCR and whole-cell variant patch clamp electrophysiology. Results: Both LAM cells and LAFs (n=3) expressed KCa 3.1 mRNA. At baseline, both LAM 621–101 cells and LAFs displayed similar membrane currents with slight outward rectification at positive potentials. Both cell types responded to the KCa 3.1 channel opener 1-ethyl-2-benzimidazolinone (1-EBIO;100 µM) with the development of characteristic KCa 3.1 whole cell currents. Furthermore, the currents were completely blocked by the selective KCa 3.1 blocker TRAM 34 (200 nM). Conclusion: LAM cells and primary LAFs express functional KCa 3.1 channels. The role of these in the development and progression of LAM nodules requires further investigation.